Sensitivity analysis of the secondary heat balance at Koeberg Nuclear Power Station - Boyes, Haydn (Department of Electrical Engineering, 2021)
At Koeberg Nuclear Power Station, the reactor thermal power limit is one of the most important quantities specified in the operating licence, which is issued to Eskom by the National Nuclear Regulator (NNR). The reactor thermal power is measured using different methodologies, with the most important being the Secondary Heat Balance (SHB) test which has been programmed within the central Koeberg computer and data processing system (KIT). Improved accuracy in the SHB will result in a more accurate representation of the thermal power generated in the core. The input variables have a significant role to play in determining the accuracy of the measured power. The main aim of this thesis is to evaluate the sensitivity of the SHB to the changes in all input variables that are important in the determination of the reactor power. The guidance provided by the Electric Power Research institute (EPRI) is used to determine the sensitivity. To aid with the analysis, the SHB test was duplicated using alternate software. Microsoft Excel VBA and Python were used. This allowed the inputs to be altered so that the sensitivity can be determined. The new inputs included the uncertainties and errors of the instrumentation and measurement systems. The results of these alternate programmes were compared with the official SHB programme. At any power station, thermal efficiency is essential to ensure that the power station can deliver the maximum output power while operating as efficiently as possible. Electricity utilities assign performance criteria to all their stations. At Koeberg, the thermal performance programme is developed to optimize the plant steam cycle performance and focusses on the turbine system. This thesis evaluates the thermal performance programme and turbine performance. The Primary Heat Balance (PHB) test also measures reactor power but uses instrumentation within the reactor core. Due to its location inside the reactor coolant system, the instrumentation used to calculate the PHB is subject to large temperature fluctuations and therefore has an impact on its reliability. To quantify the effects of these fluctuations, the sensitivity of the PHB was determined. The same principle, which was used for the SHB sensitivity analysis, was applied to the PHB. The impact of each instrument on the PHB test result was analysed using MS Excel. The use of the software could be useful in troubleshooting defects in the instrumentation. A sample of previously authorised tests and associated data were used in this thesis. The data for these tests are available from the Koeberg central computer and data processing system.